Measurement of t-channel single-top-quark production in pp collisions at √𝑠 = 5.02 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; Rodriguez Bosca, Sergi; et al. (Physics letters, 2024)
The observation of the electroweak production of single-top-quarks is made using 255 pb−1 of proton-proton collision data recorded at s=5.02 TeV with the ATLAS detector at the Large Hadron Collider. An event selection is used to identify single-top-quark candidates arising from t-channel production with the top quark decaying semi-leptonically. Events passing the selection are then used to measure the inclusive cross-section for the combined production of single-top-quarks and antiquarks, σ(tq+t¯q), and the ratio Rt between these two. They are measured to be σ(tq+t¯q)=27.1−4.1+4.4(stat.)−3.7+4.4(syst.) pb and Rt=2.73−0.82+1.43(stat.)−0.29+1.01(syst.). The individual single-top-quark (tq) and single-top-antiquark (t¯q) production cross-sections are measured to be σ(tq)=19.8−3.1+3.9(stat.)−2.2+2.9(syst.) pb and σ(t¯q)=7.3−2.1+3.2(stat.)−1.5+2.8(syst.) pb. All measurements are in good agreement with the Standard Model predictions.
Online verfügbar 16 May 2024, Version des Artikels 23 May 2024
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und viele weitere]
Gesehen am 22.09.2025